TRADUCTION PUBLICITAIRE ET MARKETING DES PRODUITS DE L’AGRO-ALIMENTAIRE NIGERIANS : UNE ETUDE DES ERREURS DE TRADUCTIONS - OKON, Dorathy Effiom; NDIFON, Mamina Mba; ORJIUGO, Olivia Chizomam (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
This article provides a statistical and textual analysis of French translations of advertising messages found on the packaging of about ten agro-food products either manufactured in Nigeria or marketed by Nigerian subsidiaries of multinational corporations. It critically examines the statements contained in these advertising messages, categorizing them into three main groups: (1) informations about the properties and virtues of the products, (2) informations concerning the manufacturer’s expertise and usage instructions for promotional products, and (3) purely advertising slogans. Based on this categorization of examined informations, the article seeks to identify translated portions of preference and measures the percentage of translation to ultimately infer the degrees of translation accuracy in these messages. It also analyzes various translation errors in these messages with respect to two advertising objectives: information and persuasion. In its analysis of the degree of translation, the article demonstrates that translations of advertising messages by Nigerian companies are highly selective. They generally retain approximately 53.08% of the conceptual content of the source language message and typically prioritize (give greater importance to) statements conveying the properties and virtues of the promoted product. The article argues that reducing the conceptual content of the source language message to over 40% theoretically and automatically diminishes the chances of informing and persuading the target audience as effectively as the original advertising message does in the source language public. The article also highlights the increasing incidence of translation errors, which further diminish the informative and persuasive potential of translated messages and naturally indicate both translation difficulties and the increasingly alarming phenomenon of charlatanism undermining the translation profession in Nigeria.